Stereotactic Radiotherapy for the Management of Refractory Ventricular Tachycardia: Promise and Future Directions - Jumeau, Raphael; Ozsahin, Mahmut; Schwitter, Juerg; Elicin, Olgun; Reichlin, Tobias; Roten, Laurent; Andratschke, Nicolaus; Mayinger, Michael; Saguner, Ardan M.; Steffel, Jan; Blanck, Oliver; Vozenin, Marie-Catherine; et al. (Frontiers in Cardiovascular Medicine, 2020)
Ventricular tachycardia (VT) caused by myocardial scaring bears a significant risk of mortality and morbidity. Antiarrhythmic drug therapy (AAD) and catheter ablation remain the cornerstone of VT management, but both treatments have limited efficacy and potential adverse effects. Stereotactic body radiotherapy (SBRT) is routinely used in oncology to treat non-invasively solid tumors with high precision and efficacy. Recently, this technology has been evaluated for the treatment of VT. This review presents the basic underlying principles, proof of concept, and main results of trials and case series that used SBRT for the treatment of VT refractory to AAD and catheter ablation.